Arbitrary order exceptional point induced by photonic spin–orbit interaction in coupled resonators - Shubo Wang (Nature Portfolio, 2019)
Exceptional points in non-Hermitian systems can enhance the performance of optical sensors. Here, Wang et al. demonstrate theoretically and experimentally that higher-order exceptional points, which would allow for yet higher sensitivities, can be realized in simple photonic resonator chains.